2020
DOI: 10.26452/ijrps.v11ispl4.3751
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Video Teaching Programme in prevention of Gestational Diabetic Mellitus among Antenatal Mothers

Abstract: Gestational Diabetic Mellitus is the type of diabetes in pregnancy. It normally shows up in the second 1/2 of pregnancy and numerous impacts fetal development rate and causes moderate foundational improvement. The goal of prevention in pregnancy to change dietary patterns, maintain balanced glucose level and to replace them with a healthy lifestyle for mother. The main purpose of this study to assess the effectiveness of video teaching programme in prevention of gestational diabetic Mellitus among antenatal mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Other studies have also been conducted, all of which showed the positive effect of the educational film on the knowledge of pregnant mothers in other health fields. A study in India showed that the use of an educational video improved pregnant mothers' knowledge of gestational diabetes (21). Another Indonesian study showed that video-based education could improve pregnant mothers' awareness of the dangers of smoking exposure (22).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also been conducted, all of which showed the positive effect of the educational film on the knowledge of pregnant mothers in other health fields. A study in India showed that the use of an educational video improved pregnant mothers' knowledge of gestational diabetes (21). Another Indonesian study showed that video-based education could improve pregnant mothers' awareness of the dangers of smoking exposure (22).…”
Section: Discussionmentioning
confidence: 99%